FREQUENCY OF ACUTE KIDNEY INJURY IN PATIENTS UNDERGOING CORONORY ARTERY BYPASS GRAFTING - Shah, Syed Murad Ali; ., Ikramullah; Khan, Ajab; Sher, Akhtar; Malik, Abdul; Ullah, Naseem; Khan, Riaz Anwar (Journal of Postgraduate Medical Institute, 2016)
Objective: To find the frequency of acute kidney injury in patients undergoing coronary artery bypass grafting. Methodology: The study was conducted in cardiovascular unit Lady Read -ing Hospital Peshawar. It was cross sectional study. Sampling technique was non probability convenient sampling. Data was collected from 20.2.2013 to 20.8.2013. Total 179 patients included in the study. All patients with known coronary artery disease were included in the study whom were planned for revascularization in the form of coronary artery bypass grafting (CABG). Post -operatively all patients' serum creatinine till 48th post op hour was observed to detect acute kidney injury. Acute Kidney Injury (AKI) was defined as more than 50 % or elevation of 0.3 mg/dl of creatinine level from base line. Results: A total of 179 patients undergoing coronary artery bypass grafting were included in the study. Average age of the patients was 46.88 years ±9.91 with range 20-60 years. Patients were divided into four groups according to age. The acute kidney injury after coronary artery bypass grafting was ob-served in 14 (7.82%) patients. Acute kidney injury was more common in old age and it was non significantly more common in male gender. Conclusion: In spite of current highly advance cardiac surgery techniques and post operative care still there is high incidence of acute kidney injury follow-ing revascularization and subsequent worst outcomes.